The Role of Customer Satisfaction as a Mediator for Service Quality and Perceived Value in Influencing Brand Loyalty Event Organizer Heaven Flow - Nugraha, Made Hadi; Hermeindito (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
The purpose of writing this thesis is to obtain empirical evidence and to analyze and explain how customer satisfaction mediates service quality and perceived value in influencing brand loyalty at event organizer service company Heaven Flow. The variables of this study consist of the dependent variable, namely service quality and perceived value, the mediating variable, namely customer satisfaction, and the dependent variable, namely brand loyalty. The sampling method used in this study is a saturated sample with 114 Heaven Flow customers as respondents. All hypotheses of this study were tested using SEM-PLS analysis using Warp-PLS version 3.0. The results of this study indicate that service quality has a positive and significant relationship to brand loyalty and customer satisfaction, perceived value has a positive and significant relationship to brand loyalty and customer satisfaction, customer satisfaction has a positive and significant relationship to brand loyalty, and customer satisfaction is able to mediate the effect of service quality and perceived value on Heaven Flow brand loyalty as an event organizer service company.